Joining of polymer-metal hybrid structures : principles and applications - Amancio Filho, Sergio T., 1976-; Blaga, Lucien-Attila (Hoboken, NJ : John Wiley & Sons, Inc., 2018)
This book introduces the concepts of joining technology for polymer-metal hybrid structures by addressing current and new joining methods. This is achieved by using a balanced approach focusing on the scientific features (structural, physical, chemical, and metallurgical/polymer science phenomena) and engineering properties (mechanical performance, design, applications, etc.) of the currently available and new joining processes. It covers such topics as mechanical fastening, adhesive bonding, advanced joining methods, and statistical analysis in joining technology--
Part I. Joining processes based on adhesion forces -- Principles of adhesive bonding -- Adhesive bonding of polymers composites to lightweight metals -- Friction spot joining -- Induction welding of metal/composite hybrid structures -- Direct joining of metal and plastic with laser -- Part II. Joining processes based on mechanical interlocking -- Principles of mechanical fastening in structural applications -- Mechanical fastening of composite and composite-metal structures -- Friction riveting of polymer-metal multi-material structures -- Staking of polymer-metal hybrid structures -- Part III. Joining processes based on direct-assembly methods -- Injection over molding of polymer-metal hybrid structures -- Ultrasonic joining of lightweight alloy/fiber-reinforced polymer hybrid structures -- Part IV. Design of experiments and statistical analysis in joining process development -- Factorial design of experiments for polymer-metal joining -- Taguchi design and response surface methodology for polymer-metal joining.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on February 09, 2018).
Keywords: Composite construction; Joints (Engineering); Composite materials; Plastics; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Composite construction; Composite materials; Joints (Engineering); Plastics; Electronic books